Patients with Ehlers–Danlos syndrome on the diagnostic odyssey: Rethinking complexity and difficulty as a hero's journey. Issue 4 (15th September 2021) - Halverson, Colin Michael Egenberger; Clayton, Ellen Wright; Garcia Sierra, Abigail; Francomano, Clair
Abstract: Patients with hypermobile Ehlers–Danlos syndrome, an hereditary disorder of the connective tissue, often face a long and difficult diagnostic odyssey in pursuit of a name for their condition. Clinicians may dismiss subjective symptoms of chronic pain, thus prolonging patients' odysseys and worsening their care and satisfaction and creating antagonisms in the patient–provider relationship. A greater understanding of patient experiences is necessary in order to decrease burdens of this relationship and to improve care. To that end, we conducted 22 in‐depth, semistructured interviews with individuals who had undergone this diagnostic odyssey. We focused on the impact that the odyssey had on their lives, both inside and outside the clinic. Through narrative analysis, we found a sort of "hero's journey" in the description of their cases, highlighting issues of uncertainty and integration as well as honoring their struggles. Interviewees had encountered difficulties in working with clinicians, in multiplying symptoms, and in negative psychosocial consequences. Attention to patients' lived experience may help to build empathy and understanding for the difficult and complex clinical situation presented by Ehlers–Danlos syndrome. Using the hero's journey as a lens onto this experience allows for a more patient‐centered approach to this understanding and has potential value for comprehension of other complex diseases and invisible illnesses.